Faktor yang Berhubungan dengan Perilaku Penggunaan Alat Pelindung Diri (APD) pada Pekerja Pemanen Kelapa Sawit di PT.X - Dea Purnama Sari Sir Dea; Syafran Arrazy; Hotmatua Peralihan; Rani Suraya; Wasiyem Wasiyem (Departemen K3 FKM Universitas Halu Oleo, 2025)
Work accidents often occur due to unsafe actions and risky work environment conditions. One effort to prevent work accidents is by using PPE. Based on observations conducted by researchers through interviews with oil palm harvesters, it is known that 3 out of 5 workers understand the use of PPE correctly. However, there are still workers who are less aware of the importance of using PPE while working. The purpose of the study was to determine the factors related to the behavior of using PPE in oil palm harvesters at PT.X. This study used a cross-sectional design, with a research sample of 71 workers and using total sampling. The analysis used was chi-square. The results of the study showed that there was a significant relationship between knowledge (p = 0.000; PR = 2.051), attitude (p = 0.000; PR = 2.431), availability of PPE (p = 0.000; PR = 2.037), training (p = 0.000, PR = 2.037), regulations (p = 0.000, PR = 2.431), and supervision (p = 0.000, PR = 2.431). The conclusion of the research results, factors related to the behavior of using PPE are knowledge, attitude, availability of PPE, training, regulations, and supervision.